2015
DOI: 10.1371/journal.pone.0118204
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Antioxidant Activity of Culturable Endophytic Fungi from Alpine Plants of Rhodiola crenulata, R. angusta, and R. sachalinensis

Abstract: Rhodiola spp. are rare and endangered alpine plants widely used as medicines and food additives by many civilizations since ancient times. Their main effective ingredients (such as salidroside and p-tyrosol) are praised to exhibit pharmacologic effects on high-altitude sickness and possess anti-aging and other adaptogenic capacities based on their antioxidant properties. In this study, 347 endophytic fungi were isolated from R. crenulata, R. angusta, and R. sachalinensis, and the molecular diversity and antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 54 publications
2
70
0
7
Order By: Relevance
“…Among these fungal strains, members in the genera Fusarium, Gibberella, Phyllosticta, Colletotrichum, Aspergillus, Penicillium, Phoma, Glomerella and Diaporthe are widely distributed in nature and have a high spore production (Mishra et al, 2012), which give them more chances to colonize a wide range of plants (Schulz and Boyle, 2005;Aly et al, 2011;Zheng et al, 2016). Moreover, species in Galactomyces (Clay et al, 2016), Cylindrocarpon (Wearn et al, 2012), Stagonosporopsis (Cui et al, 2015) and Sarocladium (Potshangbam et al, 2017) have been observed as fungal endophytes in specific plants. In particular, Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Among these fungal strains, members in the genera Fusarium, Gibberella, Phyllosticta, Colletotrichum, Aspergillus, Penicillium, Phoma, Glomerella and Diaporthe are widely distributed in nature and have a high spore production (Mishra et al, 2012), which give them more chances to colonize a wide range of plants (Schulz and Boyle, 2005;Aly et al, 2011;Zheng et al, 2016). Moreover, species in Galactomyces (Clay et al, 2016), Cylindrocarpon (Wearn et al, 2012), Stagonosporopsis (Cui et al, 2015) and Sarocladium (Potshangbam et al, 2017) have been observed as fungal endophytes in specific plants. In particular, Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant was screened [ 188 ] with the 2,2'-azinodi(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) decolorization assay and 2,2'-diphenyl-1-picrylhydrazyl (DPPH) found this EF have potential novel source of natural antioxidants. Antioxidant was screened for EF in medicinal plants Rhodiola crenulata, R. angusta, and R. sachalinensis [ 189 ]. DPPH, FRAP, and Iron chelating activity are conducted using endophytes Asperigillus niger , Penicillium sp.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Screening of 347 endophytic fungal strains isolated from rhizomes of R. crenulata, R. angusta and R. sachalinensis revealed that four endophytic fungi were capable of producing salidrosides and p-tyrosol (Cui et al, 2015). One of these endophytic fungi identifi ed as Phialocephala fortinii was able to stably produce large amounts of salidrosides and p-tyrosol, 2.3 and 2 mg/ml of culture medium, respectively (Cui et al, 2016).…”
Section: Rhodiola Spp (Crassulaceae)mentioning
confidence: 99%